Death comes to Pemberley [compact disc, unabridged] - James, P. D. (Books on Tape/Random House Audio Publishing, 2011)
Pemberley is thrown into chaos after Elizabeth Bennett's disgraced sister Lydia arrives and announces that her husband Wickham has been murdered.